Itga2b regulation at the onset of definitive hematopoiesis and commitment to differentiation. - Stephanie Dumon; David S Walton; Giacomo Volpe; Nicola Wilson; Emilie Dassé; Walter Del Pozzo; Josette-Renee Landry; Bryan Turner; Laura P O'Neill; Berthold Göttgens; Jon Frampton (PLoS ONE)
Product of the Itga2b gene, CD41 contributes to hematopoietic stem cell (HSC) and megakaryocyte/platelet functions. CD41 expression marks the onset of definitive hematopoiesis in the embryo where it participates in regulating the numbers of multipotential progenitors. Key to platelet aggregation, CD41 expression also characterises their precursor, the megakaryocyte, and is specifically up regulated during megakaryopoiesis. Though phenotypically unique, megakaryocytes and HSC share numerous features, including key transcription factors, which could indicate common sub-regulatory networks. In these respects, Itga2b can serve as a paradigm to study features of both developmental-stage and HSC- versus megakaryocyte-specific regulations. By comparing different cellular contexts, we highlight a mechanism by which internal promoters participate in Itga2b regulation. A developmental process connects epigenetic regulation and promoter switching leading to CD41 expression in HSC. Interestingly, a similar process can be observed at the Mpl locus, which codes for another receptor that defines both HSC and megakaryocyte identities. Our study shows that Itga2b expression is controlled by lineage-specific networks and associates with H4K8ac in megakaryocyte or H3K27me3 in the multipotential hematopoietic cell line HPC7. Correlating with the decrease in H3K27me3 at the Itga2b Iocus, we find that following commitment to megakaryocyte differentiation, the H3K27 demethylase Jmjd3 up-regulation influences both Itga2b and Mpl expression.